PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI MENGGUNAKAN APLIKASI ANIMAKER SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF SISWA SMP PADA MATERI LISTRIK STATIS - Nisyak, Khairun; M. Syafi’i, M. Syafi’i; Zulirfan, Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning media developed is an animated video learning media using theanimaker application as an effort to improve the cognitive abilities of junior high schoolstudents on static electricity material. valid. The research development procedure uses theADDIE model, namely the Analysis, Design, Development, Implementation, andEvaluation (evaluation) stages. As for the ADDIE model research development scheme, theanalysis stages are divided into needs analysis, curriculum analysis, and material analysis.There are two design stages, namely the making of the History board and the making of theStory board. As for the development stage (Development) is the media development andvalidation stage. The validation aspect consists of the feasibility aspect of the materialcontent, the linguistic feasibility aspect, the presentation feasibility aspect, and the graphicfeasibility aspect. The results of the second stage of validation of all aspects have receiveda minimum score of 3 for each aspect. In the media validation assessment on the feasibilityaspect of the media content, the score is 3.19 with a valid category, the linguistic feasibilityaspect gets a value of 3.35 with a valid category, the presentation feasibility aspect with ascore of 3.26 valid category, and the graphic feasibility aspect with the acquisition value of3.33 with a valid category. So from the scores that have been described, the learning mediausing the Animaker application is valid and feasible to use in the learning process.Key words: Animation learning media, Animaker Application, Static Electricity